The Early Childhood Education Teachers’ Needs of Being Able to Teach English Well - Bambang Harmanto; Heri Wijayanto; Ida Yeni Rahmawati; M. Fadlillah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
English should be introduced and taught to early childhood in a fun way. Early childhood education teachers are required to have the ability to teach English in a good and fun way. The purpose of this study is to explore the needs of being able to teach English well for the early childhood education teacher (ECET). The survey technique was conducted with 56 respondents from the ECE teachers. The survey was conducted via google form with 15 questions. The result showed that 55% of the respondents gave priority of developing instructional media and materials in the expected training. Meanwhile as many as 33% of expected training was emphasized on teaching technique as the first prominent. The only 12% who considered motivation training was very principle. All trainings they were expecting the needs of designing training concept such as duration, facilitator, methodology, material, media, and setting of places were fully considered